Proximal nitrogen reduces the fluorescence quantum yield of nitrogen-vacancy centres in diamond. (1st March 2022) - Capelli, Marco; Lindner, Lukas; Luo, Tingpeng; Jeske, Jan; Abe, Hiroshi; Onoda, Shinobu; Ohshima, Takeshi; Johnson, Brett; Simpson, David A; Stacey, Alastair; Reineck, Philipp; Gibson, Brant C; et al.
Abstract: The nitrogen-vacancy colour centre in diamond is emerging as one of the most important solid-state quantum systems. It has applications to fields including high-precision sensing, quantum computing, single photon communication, metrology, nanoscale magnetic imaging and biosensing. For all of these applications, a high quantum yield of emitted photons is desirable. However, diamond samples engineered to have high densities of nitrogen-vacancy centres show levels of brightness varying significantly within single batches, or even within the same sample. Here we show that nearby nitrogen impurities quench emission of nitrogen-vacancy centres via non-radiative transitions, resulting in a reduced fluorescence quantum yield. We monitored the emission properties of nitrogen-vacancy centre ensembles from synthetic diamond samples with different concentrations of nitrogen impurities. All samples were irradiated with high energy electrons to create high densities of nitrogen-vacancy centres relative to the concentration of nitrogen impurities. While at low nitrogen densities of 1.81 ppm we measured a lifetime of 13.9 ns, we observed a strong reduction in lifetime with increasing nitrogen density. We measure a lifetime as low as 4.4 ns at a nitrogen density of 380 ppm. The change in lifetime matches a reduction in relative fluorescence quantum yield from 77.4% to 32% with an increase in nitrogen density from 88 ppm to 380 ppm, respectively. These results will inform the conditions required to optimise the properties of diamond crystals devices based on the fluorescence of nitrogen-vacancy centres. Furthermore, this work provides insights into the origin of inhomogeneities observed in high-density nitrogen-vacancy ensembles within diamonds and nanodiamonds.